2019
DOI: 10.1007/s10803-019-04179-7
|View full text |Cite
|
Sign up to set email alerts
|

The Animal in Me: Enhancing Emotion Recognition in Adolescents with Autism Using Animal Filters

Abstract: People with autism are often characterized as having difficulties with theory of mind abilities such as emotion recognition. However, rather than being a pervasive deficit of 'mindblindness,' a number of studies suggests these difficulties vary by context, and when people with autism mindread non-human agents, such as animals or cartoons, these abilities improve. To replicate this effect, 15 adolescents with both autism and intellectual disability participated in a test of facial emotion recognition, with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Such differentiation of treatment between humans and other organisms by people with ASD is consistent with the theoretical distinction formulated by Prothmann et al in 2009 to account for the contrasting abilities of people with ASD to interact with animals, and according to which animals could be assimilated to agents of actions (i.e., communicating their intentions non-verbally via body language) and humans to agent of attitudes (i.e., using meta-representations) 28 . These results are also consistent with recent studies suggesting that ToM ability is not at a global deficit in those on the autistic spectrum but may relate to the mindreading of specifically human agents 25 , 40 .…”
Section: Discussionsupporting
confidence: 93%
“…Such differentiation of treatment between humans and other organisms by people with ASD is consistent with the theoretical distinction formulated by Prothmann et al in 2009 to account for the contrasting abilities of people with ASD to interact with animals, and according to which animals could be assimilated to agents of actions (i.e., communicating their intentions non-verbally via body language) and humans to agent of attitudes (i.e., using meta-representations) 28 . These results are also consistent with recent studies suggesting that ToM ability is not at a global deficit in those on the autistic spectrum but may relate to the mindreading of specifically human agents 25 , 40 .…”
Section: Discussionsupporting
confidence: 93%
“…However, a within-groups design would have allowed a more direct comparison of differences between cartoon and human versions of the stimulus. Indeed, work by Cross et al (2019) showed that young autistic children were significantly better at recognizing emotions from full-face pictures when they were presented in anthropomorphic filters. Finally, this study utilized a heavily female sample.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, qualitative work has shown autistic people to have a particular affinity for anthropomorphism, particularly in the context of theory of mind , and may identify with animals who are similarly viewed as 'more than human' (Davidson & Smith, 2009). Empirical work has also shown that those with higher levels of autistic traits no longer underperformed on perspective-taking tasks when the agents of interest were animals rather than humans (Cross et al, 2019). Cross et al (2019) showed that young children with a clinical diagnosis of autism and comorbid disorders, such as intellectual disability were better able to correctly recognize emotions from full-face pictures when they were presented in anthropomorphic filters.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, van der Meer et al [ 28 ] suggested how portable technology such as iPads and iPhones are viable technology aids for people in areas such as communication and transitioning skills. A recent example of this technology introduced the concept of animal filters on a mobile device to understand how the idea of mind-blindness or emotion recognition can vary in contexts[ 29 ]. Other software applications or “apps” allow the user to take a photo or video while attaching specific emotions to them, which aides in recognising the emotion in the future[ 29 ].…”
Section: Current Social Support Programsmentioning
confidence: 99%
“…A recent example of this technology introduced the concept of animal filters on a mobile device to understand how the idea of mind-blindness or emotion recognition can vary in contexts[ 29 ]. Other software applications or “apps” allow the user to take a photo or video while attaching specific emotions to them, which aides in recognising the emotion in the future[ 29 ].…”
Section: Current Social Support Programsmentioning
confidence: 99%